1990
DOI: 10.1021/ma00207a050
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in melt crystallized syndiotactic polystyrene samples

Abstract: 1539eters to being orthorhombic as observed for the planar form. It is difficult to know whether these calculated values for the kink and planar forms are close enough to permit polymorphism. They apply to the energy difference at 0 K as opposed to the free energy difference at somewhere in the region of room temperature. The energy difference of 13.4 kJ/(mol repeat) corresponds to -1 kJ/ (mol chain atom) and about 13% of the calculated lattice dissociation energy. In the case of 6-6 polyester, the calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
745
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 535 publications
(779 citation statements)
references
References 4 publications
30
745
0
Order By: Relevance
“…This phenomenon is due to the competition between melting and recrystallization processes during the heating step [47]. Furthermore, a WAXD study near the melting region of about 270°C showed that the double endothermic melting behavior of sPS was caused not by a change in the crystalline form but by a recrystallization to a more perfect crystal [48]. The normalized crystallinity of sPS in the composites, X c , is given by the Equation (1): (1) where ΔH f is the melting enthalpy of sPS in the composites, ΔH f 0 is the melting enthalpy of 100% crystalline sPS (ΔH f 0 = 53 J/g) [49] and w is the weight fraction of sPS in the composites.…”
Section: Thermal Behaviormentioning
confidence: 99%
“…This phenomenon is due to the competition between melting and recrystallization processes during the heating step [47]. Furthermore, a WAXD study near the melting region of about 270°C showed that the double endothermic melting behavior of sPS was caused not by a change in the crystalline form but by a recrystallization to a more perfect crystal [48]. The normalized crystallinity of sPS in the composites, X c , is given by the Equation (1): (1) where ΔH f is the melting enthalpy of sPS in the composites, ΔH f 0 is the melting enthalpy of 100% crystalline sPS (ΔH f 0 = 53 J/g) [49] and w is the weight fraction of sPS in the composites.…”
Section: Thermal Behaviormentioning
confidence: 99%
“…38 Figure 1a shows a typical 3D WAXD pattern for samples heated from 70 to 230°C with a heating rate of 2°C/ min. The results show the characteristic WAXD pattern of the sPS δ, γ, and R form crystals appears sequentially during the gradually heating procedure, which indicates that the sPS δ form crystals transfer into γ form and then into R form crystals.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the formations of an instable mesophase during the crystallization of sPS at lower temperature, was clearly observed in the literature [2,8]. Even if the conformational order of the chain sequences is not sufficient to give rise to discrete X-ray reflections, the presence of mesomorphic phase can be characterized by infrared spectroscopy as well as permeability tests [8].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…For this reason, the sPS β form could represent a polymeric material of industrial interest due to its high melting temperature, fast crystallization rate, good chemical and thermal resistance [2,5]. However, in spite of its thermodynamic higher stability with respect to the α form, it can be obtained only at very low under-cooling (high crystallization temperature), whereas at crystallization temperatures lower than 230°C the α form is always obtained [8]. Many attempts to obtain the β form at lower temperatures failed so far.…”
Section: Introductionmentioning
confidence: 99%